TINDAK PIDANA PENGANIAYAAN DAN KEKERASAAN TERHADAP ANAK YANG MENJADI KORBAN - Hariyono By He; Aldi Suhada; Fadlan Alfarizy; Haidar Adlil; Marvel Haholongan Tampubolon (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
A domestic violence tragedy occurred when a father allegedly abused his innocent child. This incident reflects the failure of the family's function as a protective space, turning it into a place where acts of physical and psychological harm were committed by the victim. The alleged abuse not only triggered deep trauma for the child but also raised public concern about the importance of supervision, parenting education, and child protection. This case emphasizes the need for an active role from the community, law enforcement, and social institutions to ensure justice for the victim and prevent similar incidents from happening in the future.